1997
DOI: 10.1002/j.1834-4453.1997.tb00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Losing your temper: the effect of mineral inclusions on pottery analyses

Abstract: Pottery from Buka Island, Papua New Guinea, was subjected to chemical characterisation studies using both the electron microprobe and PlXE-PIGME. I report here on the problems and limits of using chemical analyses on prehistoric pottery to assess questions concerning technology and production patterns, and address in particular the problem of compensating for the chemical noise that arises when mineral inclusions are added to a clay in the manufacturing process of pottery. This chemical noise, if not taken int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The variety of geochemical studies of ceramics worldwide (e.g., Alden et al 2006;Glascock 1992;Glascock et al 2004;Hall et al 2002;Neff 1992;Padilla et al 2006;Papachristodoulou et al 2006;Rieth et al 2007) and in the Pacific region (Ambrose 1992;Anson 1983Anson , 1986Anson , 1999Bentley 2000;Burley and Dickinson 2010;Chiu 2003;Cochrane and Neff 2006;Descantes et al 2001;Eckert and James 2011;Garling 2007;Hunt 1989;Kennett et al 2004;Summerhayes 1996Summerhayes , 1997 have clearly revealed the potential of these techniques for addressing issues of pottery production, ceramic transfer and interisland interaction. The growing number of studies that have used portable X-ray fluorescence (P-XRF) in archaeology (e.g., Cecil et al 2007;Craig et al 2007;Morgenstein 2005;Nazaroff et al 2010;Papageorgieu and Liritzis 2007;Phillips and Speakman 2009;Speakman et al 2011) confirm its utility as well as its limitations in the analysis of archaeological artifacts including ceramics.…”
Section: Introductionmentioning
confidence: 98%
“…The variety of geochemical studies of ceramics worldwide (e.g., Alden et al 2006;Glascock 1992;Glascock et al 2004;Hall et al 2002;Neff 1992;Padilla et al 2006;Papachristodoulou et al 2006;Rieth et al 2007) and in the Pacific region (Ambrose 1992;Anson 1983Anson , 1986Anson , 1999Bentley 2000;Burley and Dickinson 2010;Chiu 2003;Cochrane and Neff 2006;Descantes et al 2001;Eckert and James 2011;Garling 2007;Hunt 1989;Kennett et al 2004;Summerhayes 1996Summerhayes , 1997 have clearly revealed the potential of these techniques for addressing issues of pottery production, ceramic transfer and interisland interaction. The growing number of studies that have used portable X-ray fluorescence (P-XRF) in archaeology (e.g., Cecil et al 2007;Craig et al 2007;Morgenstein 2005;Nazaroff et al 2010;Papageorgieu and Liritzis 2007;Phillips and Speakman 2009;Speakman et al 2011) confirm its utility as well as its limitations in the analysis of archaeological artifacts including ceramics.…”
Section: Introductionmentioning
confidence: 98%
“…This suggests that the variability originates from the clay matrix. Second, both petrographic and compositional data sets generally correspond in terms of distribution and groupings, as would be expected given the documented influence of inclusions on bulk chemical compositions of homogenised ceramic samples (Arnold et al 1999;Chiu 2003b;Summerhayes 1997Summerhayes :115, 2000a. The various decorative types encountered at Mangaasi, the temper types identified at Teouma (Dickinson et al 2013) and two types identified at Vao (calcareous and placer sand) are indicated.…”
Section: Resultsmentioning
confidence: 64%
“…It is true that analysing separately the clay matrix and the inclusions can ease the comparison of ceramic samples with clay deposits in certain circumstances (e.g. Ambrose 1992;Gaffney et al 2015;Summerhayes 1997Summerhayes , 2000a. In this instance, however, the aim was not so much to identify the provenance of the raw materials but rather to describe as accurately as possible the components and the variability within the assemblages.…”
Section: La-icp-ms Analysismentioning
confidence: 99%
“…As the samples for FEGSEM analysis for this study were required to be in briquette form, this technique could then distinguish between and provide separate chemical analysis of the ceramic matrix and mineral inclusions, something that is not possible with techniques using crushed samples (see Summerhayes (1997Summerhayes ( , 2000aSummerhayes ( , 2000bSummerhayes ( , 2007 for more detail). The FEGSEM is also known for its remarkably high resolution imaging that allows the analyst to accurately examine fine details (Gnauck et al 2002;Froh 2004).…”
Section: The Scanning Electron Microscopementioning
confidence: 99%